2018
DOI: 10.29252/mcs.4.4.227
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Basic Cardiopulmonary Resuscitation Training, by the Presentation Method, on the Performance of Soldiers in Military Units

Abstract: Introduction: Cardiac arrest is one of the most common causes of mortality in Iran. The reaction of the first persons who deal with such patients in the first minutes of incidence is of great importance in the prognosis of the disease as well as death or survival of the patient.Objective: the current study aimed at examining the effect of basic cardiopulmonary resuscitation training by the presentation method on soldiers' performance. Materials and Methods:In the current experimental study conducted in 2017, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…26 Similarly, another experimental study showed the effect of teaching basic CPR techniques using demonstration method on the improvement of performance among 50 selected military organization soldiers. 24 Weak knowledge and performance among people living in rural areas is a serious warning for healthcare policymakers. Previous studies have revealed weakness in untrained people's knowledge and performance regarding basic CPR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Similarly, another experimental study showed the effect of teaching basic CPR techniques using demonstration method on the improvement of performance among 50 selected military organization soldiers. 24 Weak knowledge and performance among people living in rural areas is a serious warning for healthcare policymakers. Previous studies have revealed weakness in untrained people's knowledge and performance regarding basic CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed weakness in untrained people's knowledge and performance regarding basic CPR. [23][24][25] Similarly, students living in villages had weak knowledge and performance regarding basic CPR. 32 This shows the necessity of consideration of this crucial issue by healthcare systems worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To create the resuscitation skill checklist, various sources were consulted, including references such as pre-hospital primary medical emergencies, an introduction to pre-hospital emergency management at the scene of rescue operations and the 2021 guidelines of the European Resuscitation Council [ 18 ]. Additionally, Chegeni et al‘s study was also utilized as a valuable resource [ 19 ].…”
Section: Methodsmentioning
confidence: 99%